Bidirectional Crosstalk between C5a Receptors and the NLRP3 Inflammasome in Macrophages and Monocytes - Mikel D. Haggadone; Jamison J. Grailer; Fatemeh Fattahi; Firas S. Zetoune; Peter A. Ward (Mediators of Inflammation)
C5a is an inflammatory mediator generated by complement activation that positively regulates various arms of immune defense, including Toll-like receptor 4 (TLR4) signaling. The NOD-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome is activated by pathogen products and cellular/tissue damage products and is a major contributor of IL-1β. In this study, we investigate whether C5a modulates lipopolysaccharide- (LPS-) induced NLRP3 inflammasome activation in myeloid cells. Appearance of plasma IL-1β during endotoxemia was reduced in C5aR1-/- mice when compared to wild-type mice. In vitro, C5a significantly enhanced LPS-induced production of IL-1β in bone marrow Ly6C-high inflammatory monocytes, accompanied by augmented intracellular pro-IL-1β expression. This effect was abolished during p38 blockade by SB 203580 and in the absence of C5aR1. Conversely, C5a suppressed LPS-induced macrophage production of IL-1β, which was accompanied by attenuated levels of pro-IL-1β, NLRP3, and caspase-1 expression. C5a’s suppressive effects were negated during phosphoinositide 3-kinase (PI3K) inhibition by wortmannin but were largely preserved in the absence of C5aR1. Thus, C5a bidirectionally amplifies TLR4-mediated NLRP3 inflammasome activation in monocytes while suppressing this pathway in macrophages. However, as C5aR1 deficiency attenuates the IL-1β response to LPS challenge in vivo, our results suggest overall that C5a augments physiologic inflammasome responses.